2016
DOI: 10.1016/j.conengprac.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Control strategies for automatic generation control over MTDC grids

Abstract: Increasingly in power systems, there is a trend towards the sharing of reserves and integration of markets over wide areas in order to enable increased penetration of renewable sources in interconnected power systems. In this paper, a number of simple PI and gain based Model Predictive Control algorithms are proposed for Automatic Generation Control in AC areas connected to Multi Terminal Direct Current grids. The paper discusses how this approach improves the sharing of secondary reserves and could assist in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Many works have been done on various algorithm techniques and methods such as a flower pollination technique based AGC of interlinked power environment and cross characterized 'gbest'-mentored gravitational search and marking search algorithm for AGC of multiple area power system [8][9]. Several strategies have been made for control for automatic generation control in multi terminal DC grids [10] and other strategies such as in [11], divided model predictive control strategies with demand to power system automatic generation control and in paper [12], distributed automatic generation control using horizontal-based method for large perforation in generation of wind.…”
Section: Introductionmentioning
confidence: 99%
“…Many works have been done on various algorithm techniques and methods such as a flower pollination technique based AGC of interlinked power environment and cross characterized 'gbest'-mentored gravitational search and marking search algorithm for AGC of multiple area power system [8][9]. Several strategies have been made for control for automatic generation control in multi terminal DC grids [10] and other strategies such as in [11], divided model predictive control strategies with demand to power system automatic generation control and in paper [12], distributed automatic generation control using horizontal-based method for large perforation in generation of wind.…”
Section: Introductionmentioning
confidence: 99%
“…MPC has been shown to offer setpoint tracking and robustness performance in a range of power systems applications including secondary frequency control, typically referred to as automatic generation control (AGC) [9]- [11], and voltage control [12], [13]. Additionally, MPC has been suggested for application to the dynamic control of point-to-point HVDC links [14], [15] and for providing predictive optimal power flow for MTDC systems in [16].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, MPC has been suggested for application to the dynamic control of point-to-point HVDC links [14], [15] and for providing predictive optimal power flow for MTDC systems in [16]. Recently it was shown that MPC could be used as a means of improving AGC performance and robustness for ac areas connected to MTDC grids versus decentralised PI based techniques [11], [17]. In [11], [17], several assumptions were made.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary frequency control, typically referred to as Automatic Generation Control (AGC), coordinates the actions of various power sources over the seconds to tens of seconds scale in order to eradicate longer term frequency biases. Several PFC [3], [4] and AGC approaches have been developed for aiding in frequency control in AC networks using MTDC grids [5]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…As it is a MIMO technique, it can take full advantage of system models, and it can explicitly consider delays and system constraints. It has been shown previously that there is the potential for an improvement in overall system performance in terms of frequency regulation if MPC approaches are used versus PI controllers for AGC [7], [8].…”
Section: Introductionmentioning
confidence: 99%